Corporate Governance and Firm-specific Stock Price Crashes - Andreou, Panayiotis; Antoniou, Constantinos; Horton, Joanne G.; Louca, Christodoulos (My University, 2016)
We investigate whether ownership structure, accounting opacity, board structure & processes and managerial incentives attributes relate to future stock price crash risk. Principal component analysis on the 21 attributes that comprise these four corporate governance dimensions reveals that they can explain between 13.1% and 23.0% of a one standard deviation in crash risk. Transient institutional ownership, CEO stock option incentives and the proportion of directors that hold equity increase crash risk, whilst insiders' ownership, accounting conservatism, board size and the presence of a corporate governance policy mitigate crash risk. Overall these relationships are more pronounced in environments that accentuate agency risk.
Keywords: Agency risk; Corporate governance; Crash risk; Information environment